2020
DOI: 10.3389/fendo.2020.00077
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Substance P in the Regulation of Bone and Cartilage Metabolic Activity

Abstract: Substance P (SP) is a neuropeptide that is released from sensory nerve endings and is widely present in nerve fibers. It acts on bones and related tissues by binding to receptors, thereby regulating bone metabolism, cartilage metabolism, and fracture healing. SP has attracted widespread attention as a signaling substance that can be recognized by both the immune system and the nervous system. Previous studies have shown that bone and chondrocytes can synthesize and secrete sensory neuropeptides and express the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 80 publications
(88 reference statements)
1
42
0
Order By: Relevance
“…In bone, both osteoblasts and osteoclasts were shown to express neurokinin 1 receptors [ 318 , 326 ]. Although current evidence of SP on bone formation remains inconsistent [ 327 ], SP is proposed to stimulate osteoblast proliferation and differentiation in a dose-dependent manner while simultaneously promoting the formation and activity of osteoclasts [ 328 ]. In vivo, SP-deficiency was observed to cause a minor reduction in bone resorption but a major impairment of bone formation and mineralization [ 328 ].…”
Section: Molecular Bases Of Brain-bone Crosstalkmentioning
confidence: 99%
“…In bone, both osteoblasts and osteoclasts were shown to express neurokinin 1 receptors [ 318 , 326 ]. Although current evidence of SP on bone formation remains inconsistent [ 327 ], SP is proposed to stimulate osteoblast proliferation and differentiation in a dose-dependent manner while simultaneously promoting the formation and activity of osteoclasts [ 328 ]. In vivo, SP-deficiency was observed to cause a minor reduction in bone resorption but a major impairment of bone formation and mineralization [ 328 ].…”
Section: Molecular Bases Of Brain-bone Crosstalkmentioning
confidence: 99%
“…Evidence supporting the interactions depicted in Figure 1, as well as observations that reveal neuropeptides can impact spinal cord dorsal root ganglion mechanisms associated with sensory transmission, thereby having the potential to induce an axonal reflex response in injured tissue that may invoke further inflammatory substances to be released stems from several key publications [1,2,5,11,14,[17][18][19] . These researchers and others further reveal that osteoarthritis mononuclear cells such as T-cells and macrophages that can be found to infiltrate damaged or pathologically altered joint synovial tissues, can also heighten pro-inflammatory cytokine levels in the peripheral blood vessels as well as the synovial fluid in response to diverse neuropeptides, even if this feature is not a constant one.…”
Section: Evidence Based Observationsmentioning
confidence: 69%
“…As outlined by Li et al [17] substance P, a neuropeptide widely present in nerve fibers can impact the biology of bones and related tissues such as articular cartilage in various ways by binding to compatible receptors on their cell bodies. They can thereby potentially regulate bone and cartilage metabolism, the key tissues involved in osteoarthritis.…”
Section: Evidence Based Observationsmentioning
confidence: 99%
“…SP is a member of the mammalian tachykinin family; it serves important roles in numerous biological processes related to pain transmission, neurogenic inflammation and contraction of smooth muscle through neurokinin (NK)-1, NK-2 and NK-3 receptors on target tissue (29). SP-positive nerve fibers are widely distributed in various bone tissues, especially in metabolically active parts, such as the periosteum and the epiphyseal growth plate; cartilage membranes and chondrocytes have also been found to be SP-positive (30)(31)(32). Study of SP expression during callus differentiation in adult mice has revealed its crucial role during the physiological process of fracture healing.…”
Section: Neuropeptides Of the Sensory Nervous Systemmentioning
confidence: 99%
“…Sensory neuropeptides in cartilage physiology and osteoarthritis (OA) pathogenesis. Sensory nerve fibers have been found in the perichondrium and within the cartilage canals of rat at birth (30). It is speculated that these fibers are able to modulate the physiology and function of synovial joints and cartilage canals through trophic effects.…”
Section: Neuropeptides Of the Sensory Nervous Systemmentioning
confidence: 99%